PENGARUH BIAYA OPERASIONAL DAN PENJUALAN TERHADAP LABA PADA PERUSAHAAN PT INDOFOOD CBP SUKSES MAKMUR TBK - Cut Saidati Yahumairah; Busra Busra (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze the effect of operating costs and sales on profits at the company Pt Indofood Cbp Sukses Makmur Tbk which is listed on the IDX 2014-2023. This study uses a descriptive verification method with a quantitative approach. The population in this study were PT Indofood CBP Sukses Makmur Tbk companies listed on the IDX 2014-2023 which amounted to 10 years. The sampling technique in this study was saturated sampling technique. The data source used is secondary data, namely quarterly financial reports on the company PT Indofood CBP Sukses Makmur Tbk. The data analysis technique used is multiple linear regression analysis and uses descriptive statistical tests, classical assumption tests, significance tests (t tests and F tests) and coefficient of determination analysis using SPSS. Based on the results of this study indicate (1) Partially operating costs have no effect on profits at the company pt indofood cbp sukses makmur tbk (2) Sales partially affect profits at the company pt indofood cbp sukses makmur tbk (3) Operating costs and sales simultaneously affect profits at the company pt indofood cbp sukses makmur tbk.